Deciphering the Role of microRNAs in Large-Artery Stiffness Associated With Aging: Focus on miR-181b - Baraban, Jay M.; Tuday, Eric; Berkowitz, Dan E.; Das, Sam (Frontiers in Physiology, 2021)
Large artery stiffness (LAS) is a major, independent risk factor underlying cardiovascular disease that increases with aging. The emergence of microRNA signaling as a key regulator of vascular structure and function has stimulated interest in assessing its role in the pathophysiology of LAS. Identification of several microRNAs that display age-associated changes in expression in aorta has focused attention on defining their molecular targets and deciphering their role in age-associated arterial stiffening. Inactivation of the microRNA-degrading enzyme, translin/trax, which reverses the age-dependent decline in miR-181b, confers protection from aging-associated arterial stiffening, suggesting that inhibitors targeting this enzyme may have translational potential. As LAS poses a major public health challenge, we anticipate that future studies based on these advances will yield innovative strategies to combat aging-associated arterial stiffening.